DESIGNING 3D ANIMATION FOR DENTAL HEALTH CARE USING MDLC METHOD - Bayu Syahputra; Jimmy Pratama; Vinson, Vinson (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Health education is one of the most important thing to be learn since early age like washing hands and brushing teeth. But because of the lack of education a lot of people in the community don’t know the ways to take care of their own teeth. The consequence of lack of education create a problem for a a lot of people in the community which is tooth ache. The effort that could be done to fix the problem is to create a learning media that is easy to understand and have the capability to share information widely. Because of that, animation 3D become a choice for this research to educate people in the community about dental health and how to take care of it. The method that the researcher use in this research is qualitative interview, researcher will do an interview with a dentist to get information about how to take care of your teeth. After getting the information it will then be used to create animation 3D. the method that is being used to create animation 3D is MDLC (Multimedia Development Life Cycle) which has 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing and Distribution after the animation is finished its being shared to social media such as Youtube and Instagram. Keywords: MDLC, Animation 3D, Qualitative Interview